Genotoxicity assessment of chemical mixtures. (18th December 2018) - ,; More, Simon; Bampidis, Vasileios; Benford, Diane; Boesten, Jos; Bragard, Claude; Halldorsson, Thorhallur; Hernandez‐Jerez, Antonio; Hougaard‐Bennekou, Susanne; Koutsoumanis, Kostas; Naegeli, Hanspeter; Nielsen, Søren Saxmose; et al.
Abstract: The EFSA Scientific Committee addressed in this document the peculiarities related to the genotoxicity assessment of chemical mixtures. The EFSA Scientific Committee suggests that first a mixture should be chemically characterised as far as possible. Although the characterisation of mixtures is relevant also for other toxicity aspects, it is particularly significant for the assessment of genotoxicity. If a mixture contains one or more chemical substances that are individually assessed to be genotoxic in vivo via a relevant route of administration, the mixture raises concern for genotoxicity. If a fully chemically defined mixture does not contain genotoxic chemical substances, the mixture is of no concern with respect to genotoxicity. If a mixture contains a fraction of chemical substances that have not been chemically identified, experimental testing of the unidentified fraction should be considered as the first option or, if this is not feasible, testing of the whole mixture should be undertaken. If testing of these fraction(s) or of the whole mixture in an adequately performed set of in vitro assays provides clearly negative results, the mixture does not raise concern for genotoxicity. If in vitro testing provides one or more positive results, an in vivo follow‐up study should be considered. For negative results in the in vivo follow‐up test(s), the possible limitations of in vivo testing should be weighed in an uncertainty analysis before reaching a conclusion of no concern with respect to genotoxicity. For positive results in the in vivo follow‐up test(s), it can be concluded that the mixture does raise a concern about genotoxicity. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2019.EN-1539/full